Philosophical Origins of Methodological Nomothetism of F. de Saussure’s Concept - Luchyk, Alla; Prosianyk, Oksana; Stepanchenko, Ivan (Respectus Philologicus, 2021)
The article raises the problem of philosophical principles and origins of Ferdinand de Saussure’s views. The editors of “Course in General Linguistics”, C. Bally and A. Sechehaye, contributed to the emergence of stereotypes about Saussure as the founder of structuralism, who for the first time conceptually distinguished language and speech based on dichotomy, established the systemic nature of language as an abstract entity, developed a bilateral psychological theory of sign and divided linguistics into the synchronous and the diachronic. This prevented the synthesis of Saussure’s concept as a holistic and internally consistent anthropocentric system of views. The conceptual analysis of the fundamental theses of Saussure’s concept, given in Saussure’s autographed materials, which appeared in 2002, showed that its most important feature is that it was an anthropocentric nomothetic proposition aimed at creating the foundations for the study of human language activity as such, language as such and speech as such. The Kantian idea of anthropocentric transcendentalism can be considered the principal philosophical source of Saussure’s nomothetic project.